Physiological response of high-level female judokas measured through laboratory and field tests. Retesting the validity of the Santos test - Santos, L.; Gonzalez, V.; Iscar, M.; Brime, J. I.; Fernandez-Rio, J.; Rodriguez, B.; Montoliu, M. Á. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of the study was to measure the physiological demands of a group of high-level female judokas through laboratory tests and field tests (Tatami) and to retest the validity of the Santos test on a different population.